Mencegah Bullying: Peran Pengelolaan Kelas dalam Menciptakan Lingkungan Aman - Naufal Rafif Agustian; Astuti Darmiyanti (Journal Innovation In Education, 2025)
Bullying in the school environment is still common, this problem can cause negative effects on mental health, academic achievement of students. Safe and comfortable classroom management can prevent bullying. This research aims to examine classroom management strategies that contribute to bullying prevention and build a socially and emotionally healthy learning environment. Through literature review and analysis of classroom management approaches, this article concludes that strategies such as establishing shared classroom norms, restorative approaches, strengthening assertive communication, and empathic teacher leadership can significantly reduce the potential for bullying. The research recommends continuous teacher training in prevention-based classroom management and early intervention.